Dark Side of The Family - Jutta, Mariam (University Putra Malaysia, 2012)
Binjai or Mangifera caesia is one of the lesser known species of wild mango native to Malaysia, Borneo and Sumatra that produces fruits of superior texture and excellent taste. However, care must be taken not to come into contact with the white-coloured juice of immature binjai fruits as it is an extreme irritant upon ingestion or contact with the skin; historical records indicate its use to cause both internal and external injury.